Pengaruh Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) terhadap Kemampuan Berpikir Kritis Matematika Siswa SMA - Anggun Pramida Putri; Isnaniah Isnaniah; Rusdi Rusdi; Ulva Rahmi (Departement of Mathematics Education, 2023)
This research is motivated by observations and interviews which indicate that the learning process is still centered on the teacher, resulting in passive students and low critical thinking skills in mathematics. One effort to develop critical thinking skills is through the implementation of the Think Talk Write (TTW) cooperative learning model. The purpose of this study is to determine the significant effect of the TTW cooperative learning model on the critical thinking skills of grade XI students in SMA Negeri 1 Kecamatan Harau. This study is a pre-experimental research using the Static Group Comparison Design. The sample in this study is class XI IPS 4 as the experimental group and class XI IPS 2 as the control group. The instrument used in this study is a test of critical thinking skills in mathematics. Based on the results of data analysis using t-test and Minitab software, it can be concluded that the null hypothesis is rejected. The calculated value of t is 2.33, while the tabulated value of t is 1.67. Using Minitab software, the P-value (0.011) is less than the level of significance (0.05). Therefore, it can be concluded that